Policy Brief Penanganan Stunting di Kota Surabaya: Perspektif Pendidikan dan Kesehatan Masyarakat - Mukodi, Mukodi; Rahmawati, Deti (Jurnal Penelitian Pendidikan, 2023)
This study aims to: (1) describe and analyze the policy of handling 1000 First Day of Life (Hari Pertama Kehidupan/HPK) in Surabaya; (2) describe and analyze the handling of stunting in the education and health sectors; (3) describe and analyze the supporting and inhibiting factors for the stunting management policy in the city of Surabaya. This research type is qualitative descriptive. The object of the research was Kampung KB Putat Jaya and Kampung KB Kali Rungkut. This research was collected through observation, in-depth interviews, and documentation. The data analysis technique uses the Miles and Huberman version of the analysis flow; data reduction, data presentation, and conclusion. The handling of 1000 HPK in Surabaya was proper and appropriate. Treatment indicators are based on the specific intervention and sensitive intervention forms according to the target of toddlers who experience stunting; in Kampung KB Putat Jaya and Kampung KB Kali Rungkut. At the same time, the treatment is carried out systemically, oriented towards education in the form of socialization and education on stunting management for affected families. Then this was also carried out in the health sector through counseling and assistance to cut the stunting chain. The reduction of the aggregate stunting rate in Kelurahan Putat Jaya by 223% and Kelurahan Kali Rungkut by 276% from 2022 to 2023 is a manifestation of Surabaya's seriousness in suppressing and overcoming stunting cases through various policy programs. From an educational perspective, the handling of stunting in Surabaya is carried out using education and outreach on how to prevent and handle actions in cases of stunting under five at a set target locus. Then, handling stunting from a health perspective through counseling and health facilitation for toddlers and parents with stunting at their locus.